Anti-Pyretic Activity of Madhukadi Kwatha and Madhukadi Ghana - An Experimental Study - Prashant, Math (International Journal of Pharmaceutical & Biological Archive, 2011)
The present study was carried out to evaluate the anti-pyretic activity of Madhukadi Kwatha (decoction) and it’s Ghana (aqueous extract) in Brewer’s yeast induced pyrexia method in Wistar strain albino rats. Selected animals were randomly divided into four groups of 6 animals each. The Trial drug 1 (Madhukadi decoction) was administered orally at a dose of 4.5ml/Kg body weight and Trial drug 2 (Madhukadi aqueous extract) at a dose of 9mg/Kg body weight. Paracetamol suspension (100mg/kg body/weight) was used as a Standard anti-pyretic drug for comparison and Distilled water as Control drug. Both the trial drugs showed almost equal significance in condition of Pyrexia compared to Paracetamol. Thus Madhukadi decoction and its aqueous extract can be considered as a safe and can be potentially used in treating Pyrexia.